Young People’s Experiences of Attending a Theater-in-Education Program on Child Sexual Exploitation - May, Hannah; Kloess, Juliane A.; Davies, Kari; Hamilton-Giachritsis, Catherine E. (Frontiers in Psychology, 2021)
Child sexual exploitation and abuse (CSEA) has grave implications for the mental health and wellbeing of children and young people. It has been linked to a wide range of difficulties which may extend into adulthood. School-based prevention programs that aim to raise awareness (and thereby have the potential to prevent CSEA) are popular, however, have historically lacked robust and consistent evaluation. The purpose of the present study was therefore to explore young people’s experiences of attending a school-based theater-in-education program, and the impact this had on their awareness and understanding of CSEA. Four focus groups of between four to six participants each were conducted with young people from two co-educational State schools in the UK. The approach of Template Analysis was used to analyze the data, and revealed a number of themes related to the superordinate themes of ‘Information and Detail Delivered’ and ‘Format and Timing’. The results suggest that participants gained new awareness and understanding of aspects related to CSEA, including other forms of (criminal) exploitation, as well as how to avoid harm and what to do “if bad things happen”. Participants further reported that the theater performance/live element of the program was particularly impactful, feeling that this was delivered to them at the right time, but suggesting that younger people would also benefit from the important messages. In addition, areas for improvement were identified in terms of the delivery of the program, and the issue of victim blaming. Findings are discussed with a view to practical implications and directions for future research.